Answers

The Brainliest Answer!
2015-04-05T20:41:36+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
     2 a + 3 b + 6 c = 0
           => b = - 2 (a+3c) / 3

a x² + b x + c = 0

   x  = [ -b +- √(b² - 4 a c) ] / 2a
      = [ 2 (a + 3c)/3  +- √[ 4/9 * (a+3c)² - 4 ac ] ] / 2 a
      = [  a + 3 c  +- √[ a² +9 c² + 6ac - 9ac ] ] / (3 a)
      = [  a + 3 c  +- √ [ a² + 9c² - 3ac ] ] / (3a)

EITHER,  (a-3c)² ≤ [a² +9c² - 3ac] ≤ (a+3c)²   OR,   (a+3c)² ≤ (a²+9c²-3ac) ≤ (a-3c)²

The boundaries are for one root are :
   [ a+3c + (a-3c) ] / (3a) = 2/3  and   [a+3c + (a+3c) ]/(3a) = 2(a+3c)/(3a) = -b/a

the boundaries or limits for the other root are: 
  [ a+3c - (a-3c) ] /(3a) = 2c/a   and  [a+3c - (a+3c) ]/(3a) = 2/3


So one root is between  2/3 and -b/a
the other is between  2/3  and  2c/a

2 5 2